A possible compatibility of Buddhist and Western economics: a cohesiveness agendum to the emerging global issues / Dorji Wangchuk and Tara Subba - Wangchuk, Dorji; Subba, Tara (Faculty of Business and Management, UiTM Shah Alam, 2020)
The principles of Buddhist economics have commenced to gain impetus among the business and well-being scholars, however, with little impact on the negligence and constriction principles of Western economics. Therefore, this review article explores the conceptualism dichotomy of Buddhist economics and Western economics, and principles of Buddhist economics as a pragmatic way of attaining sustainable well-being and happiness. In addition, the article examines the reliability of Buddhist economics as an economic development policy. Articles were retrieved from the web-based databases and academic search engines using thematic key words like Buddhist economics, Western economics, well-being, happiness and global issues. The data generated through detailed reading of the 66 articles were analysed within and across using constant comparison analysis technique of QUAL approach. The findings suggest that the compatibility of Buddhist and Western economics is a cohesive solution to the emerging global issues. This article also draws attention of the policymakers and economic experts to reexamine their economic policies for the common well-being of global populace and the sustainability of the economy itself.